Improving the Regional Investment Policy Mechanism - Larisa AGUZAROVA; Fatima AGUZAROVA; Bimbolat DREEV (Communications of International Proceedings, 2020)
The article shows the improvement of the mechanism for implementing the investment policy of the region on the example of the Republic of North Ossetia-Alania. The features of the economic and geographical position of the republic and its natural resource potential are revealed.  The investment potential and investment risks of the Republic of North Ossetia - Alania are analyzed. The main directions for attracting investments have been determined. The territorial advantages of the region as a whole and in individual areas have been studied. Considered and analyzed investment projects currently being implemented in North Ossetia-Alania. The planned investment projects were considered. The main problems that hinder the systematic increase in the investment attractiveness of the region are identified and the ways of their solution are proposed. The proposed approach can be used in the development of regional investment policy.
Keywords: Methods and Tools; Mechanism; Regional Investment Policy